Japanese Reforms After World War II - Syahbuddin Syahbuddin (JURNAL PENDIDIKAN IPS, 2023)
This study aims to explain the background, direction and policy objectives of the Sukutu occupation government (SCAP) (Supreme Commander of the Allied Powers) under General Douglas MacArthur in Japan after World War II. This research is a library research with qualitative methods. Library research (library research), is research that utilizes library sources to obtain research data. The United States' occupation of Japan since 1945 was against the background of Japan's involvement in World War II which was driven by the spirit of imperialism to realize "Greater East Asian Prosperity" (Dai Toua Kyoueiken). To realize these ideals, Japan then involved itself in World War I and II. Japan's defeat in the second world war began a new era during the United States occupation in 1945-1952. President Harry Truman then appointed General MacArthur as Commander of SCAP to carry out reforms in various priority areas, namely setting up a new constitution, reforming the bureaucracy and local government systems, agrarian reform, violations of the Zaibatsu law, education reform, reforming labor organizations, and equal rights for women. The reforms implemented are aimed at America making Japan a democratic country in various fields of life, be it political, economic or social, and making Japan a peaceful, secure and peace-loving country